Mucinous Adenocarcinoma of the Colon with Clear Cell Component: A Case Report and Literature Review - Andrija Karačić; Gabrijela Stanić; Domagoj Štritof; Branko Bakula; Dubravka Jandrić; Inka Kekez (Case Reports in Pathology)
Clear cell adenocarcinomas of the colon are defined as a subtype of colorectal adenocarcinoma with clear cell morphology. A 65-year old man was admitted to a Gastroenterology Department for diagnostic evaluation of a tumor in the sigmoid colon found on CT. There, the patient developed complete bowel obstruction and was operated urgently, where intraoperatively, a large tumor in the sigmoid fixated to the lateral abdominal wall was revealed. A subtotal colectomy was performed. Histopathological analysis of the surgical specimen was conducted. The immunohistochemistry staining was positive for CEA, CDX2, and CD20 and negative for CK7, CD10, MUC2, AFP, and PAS staining. Mismatch repair protein testing was negative. The pathological diagnosis was mucinous carcinoma with a clear cell component which bears an extremely low incidence that has been scarcely reported in literature. This stresses the need for more case reports like ours to be published.